Effects of aortic root motion on wall stress in the Marfan aorta before and after personalised aortic root support (PEARS) surgery. Issue 10 (5th July 2016) - Singh, S.D.; Xu, X.Y.; Pepper, J.R.; Izgi, C.; Treasure, T.; Mohiaddin, R.H.
Abstract: Aortic root motion was previously identified as a risk factor for aortic dissection due to increased longitudinal stresses in the ascending aorta. The aim of this study was to investigate the effects of aortic root motion on wall stress and strain in the ascending aorta and evaluate changes before and after implantation of personalised external aortic root support (PEARS). Finite element (FE) models of the aortic root and thoracic aorta were developed using patient-specific geometries reconstructed from pre- and post-PEARS cardiovascular magnetic resonance (CMR) images in three Marfan patients. The wall and PEARS materials were assumed to be isotropic, incompressible and linearly elastic. A static load on the inner wall corresponding to the patients' pulse pressure was applied. Cardiovascular MR cine images were used to quantify aortic root motion, which was imposed at the aortic root boundary of the FE model, with zero-displacement constraints at the distal ends of the aortic branches and descending aorta. Measurements of the systolic downward motion of the aortic root revealed a significant reduction in the axial displacement in all three patients post-PEARS compared with its pre-PEARS counterparts. Higher longitudinal stresses were observed in the ascending aorta when compared with models without the root motion. Implantation of PEARS reduced the longitudinal stresses in the ascending aorta by up to 52%. In contrast, the circumferential stresses at the interface between the supported and unsupported aorta were increase by up to 82%. However, all peak stresses were less than half the known yield stress for the dilated thoracic aorta.